Risks and Protective Factors Associated With Mental Health Symptoms During COVID-19 Home Confinement in Italian Children and Adolescents: The #Understandingkids Study - Oliva, Salvatore; Russo, Giusy; Gili, Renata; Russo, Luigi; Di Mauro, Antonio; Spagnoli, Alessandra; Alunni Fegatelli, Danilo; Romani, Maria; Costa, Anna; Veraldi, Silvio; Manti, Filippo (Frontiers in Pediatrics, 2021)
Objective: To identify risk and protective factors for mental health symptoms associated with lifestyle changes caused by home confinement in pediatric subjects and in children and adolescents with a neuropsychiatric disorder. Study design: This was a prospective, cross-sectional study conducted from May 10 to May 31, 2020. Two online anonymous surveys were developed: population-based and clinical-based (children with neuropsychiatric disorders). Outcomes included emotional and behavioral symptoms, as assessed by psychometric scales (BPSC, PPSC, PSC, CES-DC and SCARED, respectively), and lifestyle changes during home confinement (i.e., physical activity, screen time, home schooling, reading). Results: The sample included 9,688 pediatric subjects, and 289 children and adolescents with a neuropsychiatric disorder. The presence of siblings was a protective factor in all ages. In pre- and school children: male sex, a diagnosis of autism, residency in highly affected areas, high parental educational level or job loss, and screen time (>2 h/day) were risk factors. Physical activity, home-schooling, reading, talking with other people were protective factors. Residency in highly affected areas, a diagnosis of mood disorder, parental job loss, and screen time, were associated with a worsening of the depressive symptoms, whereas physical activity, talking with other people, playing with parents were protective activities. Screen time was also a risk factor for anxiety symptoms, while physical activity, reading and talking with other people were protective factors. Conclusions: This study identified risk and protective factors for mental health symptoms associated with lifestyle changes caused by COVID-19 home confinement to promote mental well-being in pediatrics during pandemic times.